# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {y^{2}}{x y+x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+x y+x^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+x \,{\mathrm e}^{-\frac {2 y}{x}}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x -y+2}{x +y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x +3 y+1}{x -2 y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+1}{2 x +2 y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (x +y-1\right )^{2}}{2 \left (x +2\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y+\left (x^{2}+3 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+x y+\left (x +y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x}+{\mathrm e}^{y} \left (1+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )^{2}-\sin \left (x \right ) \sin \left (2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{3}-x^{3} y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x -y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y \,{\mathrm e}^{2 x}+2 x \cos \left (y\right )+\left ({\mathrm e}^{2 x}-x^{2} \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 \ln \left (x \right ) x^{2}+x^{2}+y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{3}+2+3 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )-2 \sin \left (x \right ) \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{2} x^{3}+2 y+\left (3 x^{4} y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y}+x \,{\mathrm e}^{y}+x \,{\mathrm e}^{y} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = k y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{\prime } \sqrt {1-x^{2} y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}}{x y-x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (y \cos \left (y\right )-\sin \left (y\right )+x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x}-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = \arctan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \arcsin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-3 x +2\right ) y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 \sin \left (x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}x \left (x^{2}-4\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) \left (x^{2}+1\right ) y^{\prime } = 2 x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y^{2}}{1-x^{2} y}
\] |
✓ |
✓ |
|
\[
{}x^{5} y^{\prime }+y^{5} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4 x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\tan \left (x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+1+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y \ln \left (y\right )-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \left (-4 x^{2}+1\right ) \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sin \left (y\right ) = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\tan \left (x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = y-1
\] |
✓ |
✓ |
|
\[
{}x y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 1+x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\frac {y^{\prime }}{x^{2}+1} = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2} = x +2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (1+y\right ) y^{\prime } = -x^{2}+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{2 x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}+x^{2}
\] |
✓ |
✓ |
|
\[
{}2 y-x^{3} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-3 y = x^{4}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = 2 x \csc \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y-x +x y \cot \left (x \right )+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 6 x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x \ln \left (x \right ) y^{\prime }+y = 3 x^{3}
\] |
✗ |
✗ |
|
\[
{}y^{\prime }-\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+4 y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+x y = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{3} x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{2} y^{\prime } x +y^{3} = x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = y^{4} x
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{y}-2 x y\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = y^{\prime } y^{2} {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 = x^{3} \left (y-1\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x^{2} y+y \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sin \left (2 x \right ) = 2 y+2 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x +\frac {2}{y}\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}y-x^{3}+\left (x +y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{2}-4 x +5 = \left (4-2 y+4 x y\right ) y^{\prime }
\] |
✗ |
✗ |
|
\[
{}y+y \cos \left (x y\right )+\left (x +x \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )^{2}+2 \sin \left (x \right ) \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (\sin \left (x \right ) \sin \left (y\right )-x \,{\mathrm e}^{y}\right ) y^{\prime } = {\mathrm e}^{y}+\cos \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}-\frac {\sin \left (\frac {x}{y}\right )}{y}+\frac {x \sin \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}1+y+\left (1-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+y \cos \left (x \right )+\left (3 x^{2} y^{2}+\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y}{1-x^{2} y^{2}}+\frac {x y^{\prime }}{1-x^{2} y^{2}} = 1
\] |
✓ |
✓ |
|